1987
DOI: 10.1002/kin.550190406
|View full text |Cite
|
Sign up to set email alerts
|

The O + NH3reaction: A review

Abstract: Experimental data for the reaction of 0 atoms with NH3 have been reviewed with particular attention to the possible effects of secondary reactions on the deduced rate coefficient. A reaction mechaqism was assembled and computer calculations carried out to simulate several sets of experiments. The sensitivity of the calculations to uncertainties in the various rate coefficients was assessed. Transition-state theory calculations were carried out on the rate coefficient k , for the 0 + NHs + OH + NH, reaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Both Cohen and Davidson suggested rate coefficients for NH 2 recombination based on their simulation results. Cohen adopted OH recombination kinetics for eq from an unknown source which were slightly below the limit suggested by Dransfeld et al at room temperature . While Davidson et al fitted only the rate coefficient of the eq recombination channel in their simulations, they reported that inclusion of the other pathways did not affect their simulation results .…”
Section: Nitrogen-based Fuel Oxidation and Decomposition Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Cohen and Davidson suggested rate coefficients for NH 2 recombination based on their simulation results. Cohen adopted OH recombination kinetics for eq from an unknown source which were slightly below the limit suggested by Dransfeld et al at room temperature . While Davidson et al fitted only the rate coefficient of the eq recombination channel in their simulations, they reported that inclusion of the other pathways did not affect their simulation results .…”
Section: Nitrogen-based Fuel Oxidation and Decomposition Mechanismsmentioning
confidence: 99%
“…Rate coefficients for eq were fitted based on faulty reaction mechanisms, thereby underestimating the real reaction rate. Only Perry’s work was deemed of high enough quality by Cohen when he reviewed available experimental data on the kinetics of eq in 1987 . Sutherland et al repeated Perry’s measurements at 448–841 K (0.5% difference in value) and expanded them up to 1790 K .…”
Section: Nitrogen-based Fuel Oxidation and Decomposition Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, (Blagojevic et al 2003) showed that the reaction of hydroxylamine ions, NH 2 OH + , with acetic or propanoic acid makes ionized glycine and alanine. Much earlier, from about 1960 to mid 1980s, the NH 3 +O reaction has been the subject of numerous experiments reviewed by (Cohen 1987). They have been performed at moderate temperature (450 to 850 K) in flowing and static systems (Perry 1984;Baulch et al 1984) where ground state O( 3 P) is obtained by laser photolysis, or at higher temperatures (850 to 2200 K) in flames (Fenimore & Jones 1961) or in shock tube experiments (Fujii et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the primary reaction(s) of NH 3 , it is almost certain that the first nitrogenous intermediate is the amino radical, NH 2 (Cohen, 1987; DeMore et al, 1997; Espinosa‐Garcia, 2000; Seinfeld and Pandis, 2006; Tyndall et al, 1991). As with N 2 O formation, the detailed pathways of NH 2 oxidation remain a matter of some debate in the literature (Alfassi, 1998; Inomata and Washida, 1999; Levine, 1985; Seinfeld and Pandis, 2006; Tyndall et al, 1991; Warneck, 2000).…”
Section: Resultsmentioning
confidence: 99%